Optimized wireless power transfer for moving electric vehicles by real-time modification of frequency and estimation of coupling coefficient - Yamaguchi, Kazuya; Terada, Haruto; Okamura, Ryusei; Iida, Kenichi (International Journal of Electrical and Computer Engineering (IJECE), 2025)
In order to prevent global warming, electric vehicles are increasingly recommended than gasoline-powered vehicles that have been widely used in the past. However, problems peculiar to electric vehicles exists, and their widespread utilize is not progressing in Japan and other developed countries. This study performed wireless power transfer assuming that electric vehicles are stationary on a road at some distance from an AC power supply. Frequency of a power supply has significant influence on efficiency of wireless power transfer, and it is important to adjust this value on any situation. Therefore, an experiment was conducted based on the optimal frequency expression derived in the past to confirm the correctness of the expression, finally it achieved 60% transport efficiency. Moreover, since the expression includes coupling coefficient between transmission and receiving inductors, its value must be estimated accurately. In this study, an experiment was conducted to estimate value of coupling coefficient using current and voltage values measured from outside circuits, and it was compared with a theoretical expression obtained from laws on electromagnetics.